Conceiving the Goddess Transformation and Appropriation in Indic Religions - Bapat, Jayant Bhalchandra (Monash Asia Series, 2016)
Conceiving the Goddess is an exploration of goddess cults in South Asia that embodies research on South Asian goddesses in various disciplines. The theme running through all the contributions, with their multiple approaches and points of view, is the concept of appropriation, whereby one religious group adopts a religious belief or practice not formerly its own. What is the motivation behind this? Are such actions attempts to dominate, or to resist the domination of others, or to adapt to changing social circumstances - or perhaps simply to enrich the religious experience of a group's members? In examining these questions, Conceiving the Goddess considers a range of settings: a Jain goddess lurking in a Brahminical temple, the fraught relationship between the humble Camār caste and the river goddess Gaṅgā, the mutual appropriation of disciple and goddess in the tantric exercises of Kashmiri Śaivism, and the alarming self-decapitation of the fierce goddess Chinnamastā.